(untitled) (Journal of Governance and Development (JGD), 2016)
The oceans and seas are the source of life on earth and are therefore a crucial factor in determining global climate change, global economy and hence international relations. For these reasons, ocean governance must necessarily become part and parcel of the strategies for achieving the objectives sought in the Millennium Declaration of September 2000 and the new sustainable development project. This paper highlights the essence of the Law of the Sea and hence ocean governance and the role it could have played in achieving the objectives sought in Millennium Development Goals (MDGS) in Nigeria as well as the prospects for transiting to the current Sustainable Development Agenda (SDA). The paper thus equates ocean governance by means of the evolution of the law of the sea, which has progressively developed from two major principles to attend a climax with the 1982 Convention on the Law of the Sea otherwise known as UNCLOS III. The main thrust of the paper is that the opportunities provided by the law of the sea and hence ocean governance have provided impetus that can serve Nigeria as some of the most effective strategies for achieving SDGs having missed maximization in respect to the MDGs.